Liver transplantation outcomes after transarterial chemotherapy for hepatocellular carcinoma. Issue 9 (28th March 2020) - Wallace, D; Cowling, T E; Walker, K; Suddle, A; Gimson, A; Rowe, I; Callaghan, C; Sapisochin, G; Mehta, N; Heaton, N; van der Meulen, J
Abstract: Background: Transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC) awaiting liver transplantation is widespread, although evidence that it improves outcomes is lacking and there exist concerns about morbidity. The impact of TACE on outcomes after transplantation was evaluated in this study. Methods: Patients with HCC who had liver transplantation in the UK were identified, and stratified according to whether they received TACE between 2006 and 2016. Cox regression methods were used to estimate hazard ratios (HRs) for death and graft failure after transplantation adjusted for donor and recipient characteristics. Results: In total, 385 of 968 patients (39·8 per cent) received TACE. Five-year patient survival after transplantation was similar in those who had or had not received TACE: 75·2 (95 per cent c.i. 68·8 to 80·5) and 75·0 (70·5 to 78·8) per cent respectively. After adjustment for donor and recipient characteristics, there were no differences in mortality (HR 0·96, 95 per cent c.i. 0·67 to 1·38; P =  0·821) or graft failure (HR 1·01, 0·73 to 1·40; P =  0·964). The number of TACE treatments (2 or more versus 1: HR 0·97, 0·61 to 1·55; P =  0·903) or the time of death after transplantation (within or after 90 days; P =  0·291) did not alter the outcome. The incidence of hepatic artery thrombosis was low in those who had or had not received TACE (1·3 and 2·4 per cent respectively; P =  0·235). Conclusion: TACE delivered to patients with HCC before liver transplant did not affect complications, patient death or graft failure after transplantation. Graphical Abstract: The impact of transarterial chemoembolization (TACE) on oncological outcomes and postoperative complications in the UK is not well characterized. Patients with hepatocellular carcinoma who were recipients of a liver transplant were stratified according to whether they received TACE, and its impact on post-transplant mortality, graft failure and postoperative complications was assessed. The use of TACE before liver transplantation did not significantly affect the risk of post-transplant complications, mortality or graft failure. No influence on outcomes